2013
DOI: 10.1259/bjr.20130035
|View full text |Cite
|
Sign up to set email alerts
|

CT imaging as a prognostic indicator for patients with pulmonary injury from acute paraquat poisoning

Abstract: Xing X, et al. CT imaging as a prognostic indicator for patients with pulmonary injury from acute paraquat poisoning. Br J Radiol 2013;86:20130035.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…The percentage of abnormal pulmonary CT imaging in the survivor group was lower than the non-survivor group (41.88% vs 57.45%, p = 0.025) in our study, the lesions were consisted of pulmonary segment involvement, effusion, consolidation and brosis, or rapid lesion progression. Previous study reported that CT imaging could be a prognostic indicator for patients with pulmonary injury from acute PQ poisoning [17]. However, Cox regression analysis in the present study could not identify it as an independent risk factor for the prognosis.…”
Section: Discussioncontrasting
confidence: 90%
“…The percentage of abnormal pulmonary CT imaging in the survivor group was lower than the non-survivor group (41.88% vs 57.45%, p = 0.025) in our study, the lesions were consisted of pulmonary segment involvement, effusion, consolidation and brosis, or rapid lesion progression. Previous study reported that CT imaging could be a prognostic indicator for patients with pulmonary injury from acute PQ poisoning [17]. However, Cox regression analysis in the present study could not identify it as an independent risk factor for the prognosis.…”
Section: Discussioncontrasting
confidence: 90%
“…In the present study, the ROC curve of leucocyte displayed an AUC of 0.961, which is higher than that in previous report [ 17 ] because of short poisoning time (within 8 h) after ingestion in this study. In addition, Some toxicity signs, such as renal failure [ 18 ], high lactate [ 18 ], high APACHE II score[ 18 ], high lymphocyte count [ 5 ], peripheral burning sensation [ 19 ], changes on chest radiograph [ 20 ], gastrointestinal lesion [ 21 ], hypotension, severe hypoxia, acidosis, and low Glasgow Coma Scale [ 22 ] are used to differentiate those who are likely to succumb eventually from survivors. However, the use of sensory data may not provides highly reliable and accurate estimates of severity of their poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…We find HRCT as a best modality in fully evaluating the extent of acute PQ lung injury ( Fig. 3 ) ( 30 , 31 , 32 ).…”
Section: Diagnosismentioning
confidence: 97%